2006
DOI: 10.1007/s00439-006-0134-0
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation status of PCDH11X: sexual dimorphisms in gene expression levels in brain

Abstract: Genes escaping X-inactivation are predicted to contribute to differences in gene dosage between the sexes and are the prime candidates for being involved in the phenotype observed in individuals with X chromosome aneuploidies. Of particular interest is ProtocadherinX (PCDH11X or PCDHX), a recently described gene expressed in brain. In humans, PCDH11X has a homologue on the Y chromosome and is predicted to escape from X-inactivation. Employing bisulphite sequencing analysis we found absence of CpG island methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 52 publications
3
41
0
3
Order By: Relevance
“…However, it is of interest that microarray hybridization has shown elevated expression of PCDH11XY mRNA in lymphocytes from individuals with four or five X chromosomes [Sudbrak et al, 2001]. Moreover, using PCDH11X-specific primers for RT-PCR Lopes et al [2006] have shown that expression of the X allele is twofold greater in XX females than XY males and concluded that the gene escapes X inactivation. Expression of PCDH11Y was not examined by Lopes et al [2006], but there is evidence from other work [Blanco et al, 2000] that PCDH11Y is also expressed in the brain.…”
Section: Ggactcagcttttgggaact 55mentioning
confidence: 97%
See 1 more Smart Citation
“…However, it is of interest that microarray hybridization has shown elevated expression of PCDH11XY mRNA in lymphocytes from individuals with four or five X chromosomes [Sudbrak et al, 2001]. Moreover, using PCDH11X-specific primers for RT-PCR Lopes et al [2006] have shown that expression of the X allele is twofold greater in XX females than XY males and concluded that the gene escapes X inactivation. Expression of PCDH11Y was not examined by Lopes et al [2006], but there is evidence from other work [Blanco et al, 2000] that PCDH11Y is also expressed in the brain.…”
Section: Ggactcagcttttgggaact 55mentioning
confidence: 97%
“…1) are not methylated. Bisulfite sequencing of genomic DNA from 4 KS and 2 KS-PSY individuals carried out essentially as described by Lopes et al [2006] showed that the percentage of methylated CpGs in all clones examined ranged from 0 to 7% for fragment A (CpGs 1-16) and 0-3% for fragment B (CpGs 17-22). Data were obtained by sequencing a total of 20 clones (360 CpGs) from fragment A and 22 clones (132 CpGs) from fragment B.…”
mentioning
confidence: 99%
“…Expression profiles and alternative transcripts of PCDH11X/Y gene with various brain region samples have been investigated [Blanco et al, 2000[Blanco et al, , 2003. Human females display higher levels of PCDH11X gene expression in brain tissues than males [Lopes et al, 2006]. Different cassette exons of PCDH11X/Y could affect the human brain differentially in males and females by virtue of this different expression activity.…”
Section: Discussionmentioning
confidence: 97%
“…Reverse transcription-polymerase chain reaction (RT-PCR) amplification has been used to quantify expression of alternative transcripts of PCDH11X/Y genes in sub-regions of brain and various other human tissues [Blanco et al, 2000]. Transcription activity of the PCDH11X gene in females exceeds that in males twofold, and the CpG islands of PCDH11X/Y are not methylated in humans and chimpanzees [Lopes et al, 2006]. Fluorescence in situ hybridization analysis using PCDH11X/Y specific probe has demonstrated no signals in the chimpanzee and gorilla Y chromosome [Wilson et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Para estos investigadores el candidato más idóneo sería el gen de la protocadherina 11, del que existen, consecuentemente, dos variantes, una ligada a X (PCDHX [PCDH11X]), localizada en Xq21.3, y otra ligada a Y (PCDHY [PCDH11Y]), localizada en Yp11.2, pero cuya identidad alcanza el 98.3% a nivel amioacídico (Blanco et al, 2000). La expresión de ambos genes sería diferente en los dos sexos, puesto que el gen PCDHX [PCDH11X] escapa, en particular, al proceso general de inactivación que afecta característicamente a los genes contenidos en el cromosoma X, de ahí que sus niveles de expresión en los individuos de sexo femenino dupliquen los observados en los de sexo masculino (Lopes et al, 2006). El gen PCDHY [PCDH11Y] es el resultado de un proceso de transposición al cromosoma Y de una copia del gen PCDHX [PCDH11X], el cual tuvo lugar hace entre tres y cuatro millones de años, tras la separación de la línea evolutiva que condujo a la aparición de la especie humana de la que dio lugar a las restantes especies actuales de primates (Sargent et al, 1996), de ahí que esté ausente en dichas especies (Wilson et al, 2006) y que no se observe en ellas la disparidad sexual en el grado de lateralización, ni consecuentemente de habilidad manual, que aparece característicamente en nuestra especie.…”
Section: ¿Existen Otras Evidencias Al Margen De Las De Tipo Fósil Capunclassified